Contemporary performance lighting experience, creativity and meaning - Graham, Katherine; Palmer, Scott 1958-; Zezulka, Kelli (Performance + design, 2023)
This is the first major collection of critical responses to performance lighting and includes contributions from award-winning lighting designers, researchers and artists. Showcasing recent examples of work – with case studies of lighting practices in Britain, Europe, the US and China – combined with theoretical and analytical approaches to practice, this will enrich your understanding of the role and potential of light in performance and related creative practices.